(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
The paper proposes a new design solution for regulating the distribution of the working gases in the vacuum chamber of the installation (UDP -850/4) for unbalanced magnetron sputtering, which will improve the mode and quality of application of multilayer nano-coatings. Constructive documentation for manufacturing a gas distribution system has been prepared, as well as instructions for assembly to the vacuum chamber.